Method for synthesizing cellulose nanocrystals by recycling substances

By dissolving cellulose raw materials under the action of solid acid and molten organic hydrochloride, the problems of high pollution and high cost of existing cellulose nanocrystal synthesis methods are solved, and the low-cost synthesis of cellulose nanocrystals is achieved and the reagents are recycled.

CN119505024APending Publication Date: 2025-02-25CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411840505.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing cellulose nanocrystal synthesis methods have problems such as high pollution, high cost and difficult reagents to be recycled, and there is a lack of a low pollution, low cost and reagents to be recycled.

Method used

Under the action of solid acid and molten organic hydrochloride, the amorphous phase in the cellulose raw material is dissolved, the solid is separated, and cellulose nanocrystals are obtained, and the solid acid and organic hydrochloride are recovered by anti-solvent and centrifugation.

Benefits of technology

The low-cost synthesis of cellulose nanocrystals is achieved, reducing the equipment corrosion risk and waste treatment costs, and organic hydrochloride and solid acid can be reused, further reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505024A_ABST
    Figure CN119505024A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of cellulose nanocrystals, in particular to a method for synthesizing cellulose nanocrystals with recyclable substances, which comprises the following steps: dissolving an amorphous phase in a cellulose raw material under the action of solid acid and molten organic hydrochloride, and separating solids to obtain the cellulose nanocrystals. The used chemical reagents mainly comprise organic hydrochloride, solid acid and ethanol which are common industrial chemicals and are low in price. And compared with the traditional concentrated acid, the used solid acid has low corrosion effect on instruments. According to the method, the medicine can be recycled, the organic hydrochloride and the solid acid can be recycled, the cost is further reduced, and the waste treatment cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cellulose nanocrystal preparation, and in particular to a method for synthesizing cellulose nanocrystals with recyclable materials. Background Art

[0002] Cellulose is one of the most abundant biomass resources in nature. It mainly exists in the cell walls of plants and is usually combined with lignin and hemicellulose to form lignocellulose. According to statistics, plants can produce about 10 million tons of cellulose per year. 12 Tons of cellulose. As a green and renewable resource, cellulose plays an important role in various fields, including but not limited to papermaking, textiles, food, medicine, environment and energy. At present, various biomasses represented by cellulose have attracted more and more attention due to their wide sources, low prices, non-toxicity, environmental protection and good biocompatibility.

[0003] Cellulose nanocrystals are nanoscale cellulose crystals extracted from natural cellulose. As nanomaterials, they have the characteristics of large specific surface area, so they can be stably dispersed in water to form a uniform suspension. Cellulose nanocrystals have outstanding mechanical properties, high biocompatibility, biodegradability and unique optical properties, and have broad application prospects in composite material processing, biomedicine and food processing.

[0004] At present, the main synthesis methods of cellulose nanocrystals include acid hydrolysis, enzymatic hydrolysis and mechanical methods. The acid hydrolysis method mainly uses corrosive acids such as sulfuric acid to utilize the differences in the kinetics of acid hydrolysis reactions of different crystalline phases of cellulose. The non-crystalline phase of cellulose is dissolved first, leaving cellulose nanocrystals. This method is low-cost and widely used, but the acidic reagents such as sulfuric acid used are extremely corrosive and polluting, which will cause corrosion of equipment and pollution of water bodies. The enzymatic hydrolysis method is to selectively decompose the non-crystalline phase of cellulose by cellulase to achieve the synthesis of cellulose nanocrystals. However, the use of cellulase requires special culture equipment, and has high requirements for raw materials, temperature and pH, which will greatly increase the synthesis cost. The mechanical method mainly synthesizes cellulose nanocrystals through mechanical and physical effects, including ball milling, high-pressure homogenization, etc. However, this method still needs to be used in conjunction with the chemical method, and requires special equipment for mechanical treatment of cellulose. In summary, there is currently a lack of a synthesis method for cellulose nanocrystals with low pollution, low cost and recyclable reagents. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a method for synthesizing cellulose nanocrystals with recyclable materials, which has low drug cost and can be recycled.

[0006] To achieve the above object, the present invention provides a method for synthesizing cellulose nanocrystals with recyclable materials, comprising the following steps:

[0007] Under the action of solid acid and molten organic hydrochloride, the amorphous phase in the cellulose raw material is dissolved, the solid is separated, and cellulose nanocrystals are obtained.

[0008] Optionally, the mass ratio of the solid acid to the organic hydrochloride is 1:50-500.

[0009] Optionally, the dissolution temperature is 0 to 100° C., and the dissolution time is 4 to 24 hours.

[0010] Optionally, the solid acid is selected from Amberlyst model solid acid.

[0011] Optionally, the organic hydrochloride includes one or more of cysteine ​​hydrochloride, cysteamine hydrochloride, ethanolamine hydrochloride, ethylamine hydrochloride, methylamine hydrochloride, glycine hydrochloride, lysine hydrochloride and betaine hydrochloride.

[0012] Optionally, the cellulose raw material includes natural cellulose and / or modified cellulose.

[0013] Optionally, after dissolving the amorphous phase in the cellulose raw material, a milky white turbid liquid is obtained, an anti-solvent is added to the milky white turbid liquid to precipitate the solid acid, and the solid acid is filtered to recover the solid acid.

[0014] Optionally, the anti-solvent includes one or more of ethanol, water, acetone, isopropanol, and ether.

[0015] Optionally, the filtrate obtained by filtration is centrifuged, and the supernatant is recrystallized at low temperature or the solvent is dried by heating to obtain the recovered organic hydrochloride.

[0016] Optionally, the precipitate obtained by the centrifugal treatment is washed with water and freeze-dried to obtain cellulose nanocrystals.

[0017] Compared with the prior art, the present invention provides a method for synthesizing cellulose nanocrystals with recyclable materials, comprising the following steps: dissolving the amorphous phase in the cellulose raw material under the action of solid acid and molten organic hydrochloride, and filtering to obtain cellulose nanocrystals.

[0018] Compared with the traditional cellulose nanocrystal synthesis method, the present invention has at least the following beneficial effects:

[0019] (1) The cost of the drugs used in the present invention is low: the chemical reagents used in the present invention mainly include organic hydrochloride, solid acid and common solvents, all of which are common industrial chemicals and are cheap. In addition, the solid acid used has a lower corrosive effect on equipment than traditional concentrated acid.

[0020] (2) The present invention realizes the recycling of medicines: the present invention can reuse organic hydrochlorides and solid acids, further reducing costs and reducing the cost of waste treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A flow chart of a method for synthesizing cellulose nanocrystals with recyclable materials provided by the present invention;

[0022] Figure 2 Transmission electron microscopy images and particle size distribution of synthesized cellulose nanocrystals. DETAILED DESCRIPTION

[0023] The present invention provides a method for synthesizing cellulose nanocrystals in a recyclable manner, comprising the following steps:

[0024] Under the action of solid acid and molten organic hydrochloride, the amorphous phase in the cellulose raw material is dissolved, the solid is separated, and cellulose nanocrystals are obtained.

[0025] In the present invention, organic hydrochloride is heated and melted as a solvent, wherein the free organic molecules and chloride ions are very likely to produce hydrogen bonds, which can be inserted into the hydrogen bond network of cellulose during the dissolution process of cellulose, thereby reducing the strength of the hydrogen bond network of cellulose. + It reacts with cellulose by acid hydrolysis to reduce the degree of polymerization of cellulose. The two effects complement each other and can destroy the high degree of polymerization and strong hydrogen bond network of cellulose, and jointly promote the partial dissolution of the amorphous phase in cellulose, leaving cellulose nanocrystals.

[0026] Preferably, the mass ratio of the solid acid to the organic hydrochloride is 1:50-500, more preferably 1:50-150, specifically 1:50, 1:100, 1:150, or a range value with any of the above values ​​as the upper or lower limit.

[0027] The addition amount of the cellulose raw material is preferably 0.5% to 20% of the mass of the organic hydrochloride, more preferably 1% to 10%, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range value with any of the above values ​​as the upper or lower limit.

[0028] The solid acid is capable of releasing H +The solid phase acid material is preferably an Amberlyst solid acid, which is a porous framework prepared by using styrene and divinylbenzene in the presence of a special pore-forming agent, and is a solid acid catalyst with a sulfonic acid group obtained by sulfonation. It includes but is not limited to one or more of Amberlyst-15, Amberlyst-26, Amberlyst-35, Amberlys-36, Amberlyst-45, etc.

[0029] The organic hydrochloride is a salt formed by hydrochloric acid and an organic base compound such as an amine, and preferably includes one or more of cysteine ​​hydrochloride, cysteamine hydrochloride, ethanolamine hydrochloride, ethylamine hydrochloride, methylamine hydrochloride, glycine hydrochloride, lysine hydrochloride and betaine hydrochloride.

[0030] The present invention adopts a solid acid and an organic hydrochloride system to dissolve cellulose, and has the advantages of low price, low corrosivity, low damage to equipment, reusability, easy product separation, and the like.

[0031] The above system can be applied to conventional cellulose raw materials, including but not limited to natural cellulose and / or modified cellulose, such as cotton, cotton linters, cotton pulp, microcrystalline cellulose, wood pulp, etc.

[0032] Preferably, the dissolving is performed under heating conditions.

[0033] The dissolution temperature is preferably 0 to 100°C, more preferably 70 to 100°C.

[0034] The dissolution time is preferably 4 to 24 hours, more preferably 12 to 24 hours.

[0035] Preferably, the dissolving is carried out under stirring conditions.

[0036] Preferably, the organic hydrochloride is first heated to a molten state, and then the cellulose raw material is added and fully soaked, and then the solid acid is added and heated and stirred at 0 to 90° C. for 4 to 24 hours to dissolve the cellulose raw material gradually to form a milky white turbid liquid.

[0037] The temperature at which the organic hydrochloride is heated is determined by its melting point, and is preferably 60-100°C.

[0038] The milky white solid precipitated from the milky white turbid liquid is cellulose nanocrystals, which can be collected by separation methods such as filtration and centrifugation.

[0039] Preferably, after dissolving the amorphous phase in the cellulose raw material, a milky white turbid liquid is obtained, an anti-solvent is added to the milky white turbid liquid to precipitate the solid acid, and the solid acid is recovered by filtering.

[0040] The anti-solvent preferably includes one or more of ethanol, water, acetone, isopropanol, and ether.

[0041] Preferably, double-layer gauze is used for the filtration to separate the solid acid, and the recovered solid acid particles can be directly recycled.

[0042] The volume ratio of the anti-solvent is 1 to 10 times that of the original solvent.

[0043] The filtrate obtained by the above filtration is centrifuged to obtain a supernatant which is mainly an organic hydrochloride solution. The organic hydrochloride is recovered by low-temperature recrystallization or heating to dry the solvent.

[0044] The rotation speed of the centrifuge is preferably 6000-9000 r / min, and the time of the centrifuge is preferably 1-5 min.

[0045] The temperature of the low-temperature recrystallization is preferably -70 to -90°C.

[0046] After low-temperature recrystallization, the organic hydrochloride can be recovered by filtering with filter paper.

[0047] The recovered organic hydrochloride can be reused, and the filtrate after filtration can be reused as an anti-solvent.

[0048] The precipitate obtained by the above centrifugal treatment is mainly cellulose nanocrystals. After washing, the cellulose nanocrystals can be gradually and stably dispersed in pure water to form a cellulose nanocrystal dispersion. After the cellulose nanocrystal dispersion is freeze-dried, cellulose nanocrystal powder is obtained.

[0049] Figure 1 Schematic diagram of the process of the above method.

[0050] The yield of cellulose nanocrystals obtained by the above method can reach 50%. The cellulose nanocrystal particles have a high aspect ratio, wherein the cellulose nanocrystals are about 200-1000nm long and about 1-10nm in diameter.

[0051] In order to further illustrate the present invention, the following is a detailed description in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0052] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0053] Example 1

[0054] 1. Weigh 10g of cysteine ​​hydrochloride, heat at 100℃ with magnetic stirring until it is completely melted, add 0.5g of cotton and immerse it all in the liquid. Add 0.1g of solid acid Amberlyst-15, continue heating and stirring at 100℃ for 24h, and the cotton fibers are gradually destroyed to form a milky white liquid;

[0055] 2. Add 20 ml of ethanol while hot, and a white precipitate will precipitate. Use double-layer gauze to filter the used solid acid Amberlyst-15. Recover the used solid acid Amberlyst-15 and reuse it for the next cellulose dissolution;

[0056] 3. The filtrate filtered through the double-layer gauze was centrifuged at 8000r / min for 3 minutes to separate the supernatant and the white solid precipitate. After the supernatant was collected, it was placed in a -80℃ refrigerator for 4 hours to crystallize the cysteine ​​hydrochloride in the supernatant, and the cysteine ​​hydrochloride crystals were filtered and recovered using filter paper;

[0057] 4. The white precipitate after centrifugation was washed with pure water to obtain a stable dispersion of cellulose nanocrystals. 0.305 g of cellulose nanocrystal powder was synthesized by freeze-drying, with a yield of 61.0%.

[0058] Figure 2 Figure a is a transmission electron microscope image of the synthesized cellulose nanocrystals. It can be seen that the synthesized cellulose nanocrystals have a nanorod-like structure with a length of 200 to 1000 nm and a diameter of 1 to 10 nm.

[0059] Figure 2 Figure b is the hydrated particle size distribution diagram of the synthesized cellulose nanocrystals. It can be seen that the size distribution of the synthesized cellulose nanocrystals is between 200 and 1000 nm.

[0060] Example 2

[0061] 1. Weigh 10g of cysteamine hydrochloride, heat at 70℃ with magnetic stirring until it is completely melted, add 0.5g of cotton linters and immerse all of them in the liquid. Add 0.1g of solid acid Amberlyst-15, continue heating and stirring at 70℃ for 24h, and the cotton linters will gradually dissolve to form a milky white liquid;

[0062] 2. Add 20 ml of ethanol while hot, and a white precipitate will precipitate. Use double-layer gauze to filter the used solid acid Amberlyst-15. Recover the used solid acid Amberlyst-15 and reuse it for the next cellulose dissolution;

[0063] 3. The filtrate portion filtered through double-layer gauze was centrifuged at 8000r / min for 3 minutes to separate the supernatant and the white solid precipitate. After the supernatant was collected, it was placed in a -80℃ refrigerator for 4 hours to crystallize the cysteamine hydrochloride in the supernatant, and the cysteamine hydrochloride crystals were filtered and recovered using filter paper;

[0064] 4. The white precipitate after centrifugation was washed with pure water to obtain a stable dispersion of cellulose nanocrystals. 0.379 g of cellulose nanocrystal powder was synthesized by freeze-drying, with a yield of 75.8%.

[0065] Transmission electron microscopy showed that cellulose nanocrystals are about 200nm to 1000nm long and about 1 to 10nm in diameter.

[0066] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for synthesizing cellulose nanocrystals in a recyclable manner, comprising the following steps: Under the action of solid acid and molten organic hydrochloride, the amorphous phase in the cellulose raw material is dissolved, the solid is separated, and cellulose nanocrystals are obtained.

2. The method according to claim 1, characterized in that The mass ratio of the solid acid to the organic hydrochloride is 1:50-500.

3. The method according to claim 1, characterized in that The dissolution temperature is 0 to 100° C., and the dissolution time is 4 to 24 hours.

4. The method according to claim 1, characterized in that: The solid acid is selected from Amberlyst solid acid.

5. The method according to claim 1, characterized in that The organic hydrochloride includes one or more of cysteine ​​hydrochloride, cysteamine hydrochloride, ethanolamine hydrochloride, ethylamine hydrochloride, methylamine hydrochloride, glycine hydrochloride, lysine hydrochloride and betaine hydrochloride.

6. The method according to claim 1, characterized in that The cellulose raw material includes natural cellulose and / or modified cellulose.

7. The method according to claim 1, characterized in that After the amorphous phase in the cellulose raw material is dissolved, a milky white turbid liquid is obtained, an anti-solvent is added to the milky white turbid liquid to precipitate solid acid, and the solid acid is recovered by filtering.

8. The method according to claim 7, characterized in that The anti-solvent includes one or more of ethanol, water, acetone, isopropanol, and ether.

9. The method according to claim 7, characterized in that: The filtrate obtained by filtration is centrifuged, and the supernatant is recrystallized at low temperature or the solvent is dried by heating to obtain the recovered organic hydrochloride.

10. The method according to claim 9, characterized in that The precipitate obtained by the centrifugal treatment is washed with water and freeze-dried to obtain cellulose nanocrystals.

Citation Information

Patent Citations

  • Recyclable solvent for dissolving cellulose and recovery method thereof

    CN115636977A